2011
DOI: 10.1002/pola.24837
|View full text |Cite
|
Sign up to set email alerts
|

Alumina additives for fast iron‐mediated AGET ATRP of MMA using onium salt as ligand

Abstract: Three kinds of alumina (acidic, neutral, and basic Al2O3) were effective as additives for the control and rate enhancement of iron‐mediated AGET (activators generated by electron transfer) ATRP (atom transfer radical polymerization) of methyl methacrylate (MMA) in the presence of limited amount of air, using FeCl3·6H2O as the catalyst, tetrabutylammonium bromide or tetra‐n‐butylphosphonium bromide as the ligand, ethyl 2‐bromoisobutyrate as the initiator, and ascorbic acid as the reducing agent. The conversion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 103 publications
1
26
0
Order By: Relevance
“…The above results demonstrated that under the polymerization conditions, the thermal initiation dominated the initiation process, and the contribution of St‐derived alkyl halide initiator generated from the addition reaction between St with Br 2 was minor and negligible. The molecular weights were controlled and regulated by the in situ ‐generated FeBr 3 from the reaction of Fe(0) and Br 2 , which can act as an effective ATRP mediator via a dynamic equilibrium between FeBr 3 /P n ·and FeBr 2 /P n ‐Br 34–38. The proposed mechanism was depicted in Scheme .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above results demonstrated that under the polymerization conditions, the thermal initiation dominated the initiation process, and the contribution of St‐derived alkyl halide initiator generated from the addition reaction between St with Br 2 was minor and negligible. The molecular weights were controlled and regulated by the in situ ‐generated FeBr 3 from the reaction of Fe(0) and Br 2 , which can act as an effective ATRP mediator via a dynamic equilibrium between FeBr 3 /P n ·and FeBr 2 /P n ‐Br 34–38. The proposed mechanism was depicted in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with Cu, Fe is more desirable owing to its low toxicity, readily abundance, and biocompatibility 28–33. In ATRP, Fe can be used in its divalent state as activator or trivalent state as deactivator in the presence of reducing agent or free radical initiator 34–37. In 2009, Xue et al reported a novel Fe III ‐mediated ATRP without any additional reducing agent or free radical initiator 38.…”
Section: Introductionmentioning
confidence: 99%
“…The immiscibility and miscibility of inorganic bases and ILs in organic solvents respectively motivated the researchers towards application of basic ILs (basic ILs) in polymerization process [36,37]. 1-Butyl-3-methylimidazolium ILs with basic anions such as hydroxide, carbonate, bicarbonate, and phosphate were used as additives replacing inorganic bases such as NaOH, Fe(OH) 3 , and basic Al 2 O 3 in AGET ATRP polymerization of MMA [39,40].…”
Section: Radical Polymerization In Ilsmentioning
confidence: 99%
“…ILs were also used as solvents in reverse ATRP (RATRP) [30][31][32][33][34], as initiators for continuously activator generated ATRP (ICAR ATRP) [35], and as activators generated by electron transfer ATRP (AGET ATRP) [36][37][38][39][40][41][42][43]. ILs of the type 1-alkyl-3-methylimidazolium with different alkyl chains such as butyl, hexyl, octyl, and dodecyl and anions such as tetrafluoroborate and hexafluorophosphate (IL-I) were used extensively as solvents for RATRP polymerization [30][31][32][33][34].…”
Section: Radical Polymerization In Ilsmentioning
confidence: 99%
“…For example, in [90], three kinds of alumina (acidic, neu tral, and basic Al 2 O 3 ) were used as additives to increase the rate of the AGET polymerization of MMA cata lyzed by FeCl 3 ⋅ 6H 2 O, tetrabutylammonium bromide or tetra n butylammonium bromide, and ascorbic acid. Polymerization proceeded both without air and in the presence of atmospheric oxygen.…”
Section: Ways To Increase the Efficiency Of Controlled Synthesis Of Pmentioning
confidence: 99%